2014
DOI: 10.1097/won.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Cues to Urinary Urgency and Urge Incontinence

Abstract: Cues associated with urgency incontinence and urgency were frequently reported by both groups. However, responding to cues was significantly more frequent among those who had been diagnosed with OAB. These findings may have implications for the diagnosis and treatment of urinary urgency incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…It appears that higher scores on the TB-WEB scale provoked higher sensitivity to urinary cues that, in turn, were associated with more intense lower urinary tract symptoms in older women. These findings are similar to those in previous reports on the relation of urinary cues to OAB but add information about their relation to UI [8][9][10]. In light of recent findings that visual triggers for urinary urgency specific to an individual lead to increased activity in the prefrontal cortex and limbic systems [11], our findings suggest a mechanism for how urinary cues come to affect brain-bladder connections.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It appears that higher scores on the TB-WEB scale provoked higher sensitivity to urinary cues that, in turn, were associated with more intense lower urinary tract symptoms in older women. These findings are similar to those in previous reports on the relation of urinary cues to OAB but add information about their relation to UI [8][9][10]. In light of recent findings that visual triggers for urinary urgency specific to an individual lead to increased activity in the prefrontal cortex and limbic systems [11], our findings suggest a mechanism for how urinary cues come to affect brain-bladder connections.…”
Section: Discussionsupporting
confidence: 91%
“…Environmental stimuli are also related to the experience of urges to urinate. A series of studies [8][9][10] has shown that people report that they associate a variety of stimuli, such as arriving at their front door, being near a familiar bathroom, and the sound of running water, with the urge to urinate. These associations are consistent with Pavlovian or classical conditioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the frequency of patients with UUI reporting that certain scenarios in "real life" increase urgency and leakage, 1,2,5,6 the aim of this pilot study was to assess the feasibility of identifying these situations, and to test ways to recreate them and systematically assess reactivity to those cues. Via telephone interview we identified seven common urgency cues and three common safe scenarios, which we then used to develop a standardized set of pictorial cues to present in a computer-based cuereactivity questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies revealed that specific TBs, that is, delayed voiding, are related to specific health beliefs 13 and women's reports of more urinary urge cues are related to bladder storage LUTS, that is, urinary urgency and urgency incontinence. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%